Prosthesis-User-in-the-Loop: A user-specific biomechanical modeling and simulation environment - Wojtusch, J.; Christ, O.; Wolff, K.; Von Stryk, O.; Rinderknecht, S.; Vogt, J.; Beckerle, Philipp (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2012)
In this paper, a novel biomechanical modeling and simulation environment with an emphasis on user-specific customization is presented. A modular modeling approach for multi-body systems allows a flexible extension by specific biomechanical modeling elements and enables an efficient application in dynamic simulation and optimization problems. A functional distribution of model description and model parameter data in combination with standardized interfaces enables a simple and reliable replacement or modification of specific functional components. The user-specific customization comprises the identification of anthropometric model parameters as well as the generation of a virtual three-dimensional character. The modeling and simulation environment is associated with Prosthesis-User-in-the-Loop, a hardware simulator concept for the design and optimization of lower limb prosthetic devices based on user experience and assessment. For a demonstration of the flexibility and capability of the modeling and simulation environment, an exemplary application in context of the hardware simulator is given. © 2012 IEEE.
CRIS-Team Scopus Importer:2021-09-24